Kualitas Audit, Profitabilitas, Leverage Dan Struktur Kepemilikan Terhadap Opini Audit Going Concern - Ahmad Juanda; Thomas Fernandez Lamury (Jurnal Akademi Akuntansi, 2021)
This research is aimed to find empirical evidence of the effect of audit quality, profitability, leverage and ownership structure on going concern audit opinions on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017 – 2019. The population of this study is 187 listed manufacturing companies. on the Indonesia Stock Exchange in 2017 – 2019. Using purposive sampling, the sample from this study became 100 manufacturing companies with sample criteria: manufacturing companies listed on the Indonesia Stock Exchange in 2017 – 2019 with complete data and no losses during the period study. This research method uses a quantitative approach with data analyzed using logistic regression. The results obtained are that Audit Quality and Leverage partially have a significant effect on Going Concern Audit Opinions in manufacturing companies listed on the Indonesia Stock Exchange in 2017 - 2019. Profitability and Ownership Structure partially have no effect on Going Concern Audit Opinions in listed manufacturing companies. on the Indonesia Stock Exchange in 2017 – 2019. Audit Quality, Profitability, Leverage, Ownership Structure simultaneously affect the Going Concern Audit Opinion in manufacturing companies listed on the Indonesia Stock Exchange in 2017 – 2019.